STRATIGRAFIA E PALEOGEOGRAFIA DEL CARNICO LOMBARDO (SONDAGGIO S. GALLO, VALLE BREMBANA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Studies on the most southern and complete Carnian sequence of the Bergamasc Alps (S. Gallo well) and of several exposed stratigraphic sections throw new light on the paleogeographic evolution and the metallogenesis of the Pb—Zn—Fluorite—Barite Gorno district. In the Early Carnian (Calcare Metallifero Bergamasco and Basal Tongue of the Gorno Fm.) , an open lagoon with mixed calcareous—terrigenous sedimentation passed northward to carbonate tidal flats and was fringed by karstified carbonate paleo—highs. Next, the great supply of terrigenous detritus from a southern volcanic belt brought about the progradation of a fluviodeltaic body (Val Sabbia Sandstone) and confined carbonate sedimentation to an outer zone.
Keywords: Stratigraphy; Paleogeography; Upper Triassic; Deltaic sandstones; Lagoonal and peritidal carbonates; Metallogenesis; Transition matrix statistics.